Sustainable Growth of Greenhouses: Investigating Key Enablers and Impacts - Nodira Saidaxmedova; Murodjon Mamatkulov; Khavakhon Rakhimova; Nazimjon Askarov; Shakhnoza Khamrayeva; Abdukholik Mukhtorov; Shakhida Khodjimukhamedova; Talantbek Madumarov; Khurshida Kurbanova; Akmal Durmanov (Emerging Science Journal, 2023)
The main objective of this study was to identify the factors influencing greenhouse development in Uzbekistan. Supported by the literature, the conceptual model of the study hypothesized that economic viability, supportive infrastructure services, enablers, and competition impacts positively affect greenhouse development. Therefore, a questionnaire was administered among 200 individuals working in greenhouses across the Tashkent, Syrdarya, Jizzakh, and Bukhara regions. Quantitative empirical evidence using structural equation modeling revealed that enablers and competition impacts have a significant positive influence on greenhouse development. However, economic viability and supportive infrastructure services did not have a direct impact, although they indirectly contributed to the overall growth and functioning of the greenhouse industry. The study provides theoretical contributions by identifying key factors influencing greenhouse development and offers practical recommendations for policymakers and stakeholders to foster an enabling environment, manage competition effectively, enhance supportive infrastructure, promote international collaboration and investment, encourage research and development, and strengthen market linkages. This research contributes to the understanding of greenhouse development in Uzbekistan and provides insights for evidence-based decision-making and strategic planning in the industry. Doi: 10.28991/ESJ-2023-07-05-014 Full Text: PDF